2021
DOI: 10.3390/foods10092006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Microbiota on Flavor Perception: From Food Processing to In-Mouth Metabolization

Abstract: Flavor perception during food intake is one of the main drivers of food acceptability and consumption. Recent studies have pointed to the oral microbiota as an important factor modulating flavor perception. This review introduces general characteristics of the oral microbiota, factors potentially influencing its composition, as well as known relationships between oral microbiota and chemosensory perception. We also review diverse evidenced mechanisms enabling the modulation of chemosensory perception by the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 102 publications
(197 reference statements)
0
28
0
Order By: Relevance
“…Furthermore, assessment of missing teeth not due to trauma or orthodontics is an indicator of past periodontal disease, and a recent study found 70% of COVID-19 patients had lost teeth due to severe periodontal disease [11]. The evaluation of dental restorations and oral appliances was related to the role of oral biofilms in modulating taste and smell function via retronasal olfaction [23,24]. Factors such as appliance wearing, tooth brushing habits and the restorative state of the dentition are recognised as modifying the oral microbiome, which, in turn, may alter oral function [25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, assessment of missing teeth not due to trauma or orthodontics is an indicator of past periodontal disease, and a recent study found 70% of COVID-19 patients had lost teeth due to severe periodontal disease [11]. The evaluation of dental restorations and oral appliances was related to the role of oral biofilms in modulating taste and smell function via retronasal olfaction [23,24]. Factors such as appliance wearing, tooth brushing habits and the restorative state of the dentition are recognised as modifying the oral microbiome, which, in turn, may alter oral function [25].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] illustrates examples of research into the relationship between taste, food choices, and eating. Other factors such as smell/odor detection, satiety, and addictions follow in subsequent tables.…”
Section: Who Behavioral Modification #1: Eat a Healthy Diet (In Spite Of The Microbiota-driven Sense Control)mentioning
confidence: 99%
“…Comprehensive coverage of the multiple pathways through which both taste and smell are affected by microbiota. [112] For the purpose of considering the inter-relationships between regulation of the senses, food behavior, and risk of NCDs, I will use obesity/metabolic syndrome as a specific example. Obesity is one of the key drivers of the ongoing NCD epidemic and is one of the first NCDs to arise during childhood.…”
Section: Taste and Smell Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…What we get from food depends upon what we eat but also on what the microbes do as per extraction and metabolism of the food. Table 2 [96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] illustrates examples of research into the relationship between taste, food choices, and eating. Other factors such as smell/odor detection, satiety, and addictions follow in subsequent tables.…”
Section: Who Behavioral Modification #1: Eat a Healthy Diet -(In Spite Of The Microbiota-driven Sense-diet Cycle)mentioning
confidence: 99%